The effect of a self-management training based on the 5As model on the sexual satisfaction of Iranian women: A randomized clinical trial - Zahra Haghighi; Ashraf Kazemi; Marjan Beigi (Journal of Health Psychology, 2026)
Sexual satisfaction is associated with sexual health and overall quality of life. This study aimed to determine the effect of self-management training based on the 5As model on the sexual satisfaction of Iranian women. This randomized clinical trial enrolled 82 women of reproductive age into 2 groups: a control group and an intervention group. Randomization of participants was performed using a random number table. The intervention was based on the 5As self-management model. The data collection tool included the Larson Sexual Satisfaction Questionnaire. SPSS-20 statistical software and inferential statistical tests were used to analyze the data. After the intervention, the mean sexual satisfaction score in the intervention group was significantly higher than before the intervention ( p < 0.05). However, this difference was not significant in the control group ( p > 0.05). Implementing the 5As self-management intervention can improve women’s sexual satisfaction; consequently, the use of this intervention model is recommended to health providers.